Odrębne elementy środowiska rodzinnego i pozarodzinnego a kształtowanie się różnic psychicznych między rodzeństwem: Potrzeba nowego paradygmatu badań - Radochoński, Mieczysław (Wydawnictwo Naukowe UAM, 2002)
The review of recent literature in the field of family science shows a growing interest in the role of nonshared environment in development of children growing up in the same family. The nonshared environmental influences make siblings rather different than similar. At the same time relatively modestprogress has been made in the identification of specific aspects of the familial and extrafamilial environment responsible for differentiated experiences of children. For example, if in the same family parents treat children differently, such differentiation accounts for only a relatively small amount of nonshared environmental influences. Also peer influence and other extrafamilial experiences are important elements o f whole nonshared environment. More empirical researches are needed in order to explain why siblings reared in the same family are often so different. The results of such investigations could possibly prove that most environmental variance affecting the development o f children, both psychologically normal or disordered, is not shared by siblings. Such possible conclusion makes that implementation of a new kind of researches is an important and urgent proposition.
The role of nonshared familial and extrafamilial environment in shaping o f psychological differences among siblings: A need for new type of research